Beyond Globalization and Global Justice: Development Theory and Practice. - Hassoun, Nicole (Analysis, 2014)
The author responds to the critics offered by authors including Miriam Ronzoni, Fernando Tesón and Gillian Brock for the book "Globalization and Global Justice: Shrinking Distance, Expanding Obligations." It mentions the conception of legitimacy, efforts taken by coercive international institutions and the requirement of justice for legitimacy. It also mentions theories of coercion libertarians, efforts taken by the World Trade Organization (WTO) and efforts to reduce poverty.